2020
DOI: 10.3389/fphys.2020.608880
|View full text |Cite
|
Sign up to set email alerts
|

Building the Border: Development of the Chordate Neural Plate Border Region and Its Derivatives

Abstract: The paired cranial sensory organs and peripheral nervous system of vertebrates arise from a thin strip of cells immediately adjacent to the developing neural plate. The neural plate border region comprises progenitors for four key populations of cells: neural plate cells, neural crest cells, the cranial placodes, and epidermis. Putative homologues of these neural plate border derivatives can be found in protochordates such as amphioxus and tunicates. In this review, we summarize key signaling pathways and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 218 publications
(304 reference statements)
1
25
0
Order By: Relevance
“…Many previous studies showed that as the embryonic ectoderm gradually resolves into four distinct domains, numerous TFs are expressed in overlapping patterns that eventually segregate during neurulation into NP, NC, PPR and Epi, each of which characteristically expresses a subset of these TFs (reviewed in Moody and LaMantia, 2015;Seal and Monsoro-Burq, 2020;Thawani and Groves, 2020;Schlosser 2021). It is commonly posed that the overlapping expression domains are sharpened into distinct domains by repressive interactions between these TFs, similar to the interactions between gap genes during segmentation in Drosophila (reviewed in Jaeger, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many previous studies showed that as the embryonic ectoderm gradually resolves into four distinct domains, numerous TFs are expressed in overlapping patterns that eventually segregate during neurulation into NP, NC, PPR and Epi, each of which characteristically expresses a subset of these TFs (reviewed in Moody and LaMantia, 2015;Seal and Monsoro-Burq, 2020;Thawani and Groves, 2020;Schlosser 2021). It is commonly posed that the overlapping expression domains are sharpened into distinct domains by repressive interactions between these TFs, similar to the interactions between gap genes during segmentation in Drosophila (reviewed in Jaeger, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…It is well appreciated that the embryonic ectoderm becomes separated into neural and non-neural domains in response to signaling gradients of various growth factors, in particular BMP, Wnt and FGF (reviewed in Stuhlmiller and Garcia-Castro, 2012;Saint-Jeannet and Moody, 2014;Pla and Monsoro-Burq, 2018;Streit, 2018;Schlosser, 2021). By the time that the neural tube closes four domains -NP, NC, PPR and Epi-can be distinguished by a distinct suite of TFs that are thought to impose domain-specific identity (reviewed in Milet and Monsoro-Burq, 2012;Moody and LaMantia, 2015;Streit, 2018;Seal and Monsoro-Burq, 2020;Thawani and Groves, 2020). However, a number of studies have shown that the TFs that we used in our study as landmarks of these four domains are not exclusively expressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NCCs are a transient embryonic cell lineage originating from the border between the ectoderm and the neuroectoderm under the control of the right dose of BMP-SMAD signaling, all along the anterior-posterior axis of the embryo at its dorsal midline [ 164 , 165 , 166 , 167 , 168 ]. These cells undergo EMT, delaminate, migrate extensively, and differentiate into ectomesenchymal cell types, including neurons and glial cells of the PNS, pigment cells, smooth muscle cells, craniofacial cartilage and bone [ 169 , 170 ], and dental pulp cells [ 171 ].…”
Section: Zeb2 In the Development Of Nervous Systems In Vertebratesmentioning
confidence: 99%